2021
DOI: 10.1039/d0ra10694a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of g-C3N4/TiO2 nanostructures for enhanced photocatalytic reduction of U(vi) in water

Abstract: Photocatalytic technology based on g-C3N4/TiO2 is a valid solution for the remediation of wastewater containing uranium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…As shown in Figure S4, the g-C3N4/TiO2 composite shows a hysteresis loop with a type H3 shape and shifts at high relative pressures (P/P0) between 0.8 and 1.0, which suggests a mesoporous structure. Mesoporosity is typical of wrinkled, sheetlike particles, and this result is consistent with SEM images [30]. The surface area was 15.43 m 2 g −1 , higher than obtained in our previous study (Kumar et al [31]) for sole g-C3N4 after solvothermal treatment.…”
Section: Brunauer-emmett-teller (Bet) Analysissupporting
confidence: 91%
“…As shown in Figure S4, the g-C3N4/TiO2 composite shows a hysteresis loop with a type H3 shape and shifts at high relative pressures (P/P0) between 0.8 and 1.0, which suggests a mesoporous structure. Mesoporosity is typical of wrinkled, sheetlike particles, and this result is consistent with SEM images [30]. The surface area was 15.43 m 2 g −1 , higher than obtained in our previous study (Kumar et al [31]) for sole g-C3N4 after solvothermal treatment.…”
Section: Brunauer-emmett-teller (Bet) Analysissupporting
confidence: 91%
“…Recently, Z-scheme g-C 3 N 4 /TiO 2 photocatalyst has been applied in reduction of U(VI), which has achieved gratifying results, Jiang et al reported that g-C 3 N 4 /TiO 2 showed excellent photocatalytic property of U(VI) reduction and As(III) oxidation under simulated sunlight irradiation ( Jiang et al 2018). The preliminary study of our research group found that g-C 3 N 4 /TiO 2 had significant photocatalytic effect on U(VI) reduction under ultraviolet light irradiation (Liu et al 2021). Dai et al reported that ZnFe 2 O 4 /g-C 3 N 4 could efficient removal of U(VI) via simultaneous adsorption and photoreduction under visible LED light irradiation (Dai et al 2021).…”
Section: Introductionmentioning
confidence: 85%
“…The 10% g-C3N4/TiO2 sample shows the best catalytic performance because of the low band gap values (2.78 eV) compared to the other materials (TiO2 (3.11 eV) and 30% g-C3N4/TiO2, (2.99 eV)) evaluated from Diffuse Reflectance Spectra, which can lead to an enhancement of the absorption of UV light. Both composite materials possess higher degradation activity than pure TiO2, which highlight the synergetic effect between the two raw materials through the electron-hole separation [42,43]. In addition, the performance of composite material revealed that A10 is better than A30, meaning an optimal value of g-C3N4 loading is 10%.…”
Section: Optical Absorption Studies (Uv-vis Diffuse Reflectance)mentioning
confidence: 91%